ANALYSIS OF THE FINANCIAL MANAGEMENT OF SUPPLEMENTARY PENSION FUNDS IN ECUADOR - Gallegos Santillán, Doris Nataly (2016)
The purpose of this research was to develop a methodology that allows the financial management analysis of the supplementary unemployment and retirement funds of Ecuador. The Organic Social Security Law (Official Register, Supplement 587, of May 11, 2009) was considered as legal framework as well as the Reforming Law to the Social Security Law and the Bank of the Ecuadorian Social Security Institute (Official Register No. 379, November 20, 2014). In order to structure this proposal, the PERLAS method was used-proposed by the World Council of Savings and Credit Cooperatives (WOCCU) in the 1980s. Because both these cooperatives and the complementary funds have in common the establishment of an association of persons to satisfy economic, social and cultural needs through joint ownership; and in terms of these funds, counting on a complementarity to the benefits provided by the obligatory social security system, for social security and financial support in situations of unemployment and / or retirement. This methodology was successfully applied in the Social Security Supplementary Closed Fund of the National University of Chimborazo, because it allowed to monitor its financial structure; and at the same time, to be a tool for an adequate and timely decision making, being thus a reference for other similar institutions.